Penerapan Prinsip Komunikasi Islam Badan Kesatuan Bangsa dan Politik dalam Menjalin Kerukunan Organisasi Kemasyarakatan di Kota Binjai - Putri Anggria Ningsih Rangkuti; Rubino Rubino (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
This research was conducted to explain and inform the application of Islamic communication principles of the National Unity and Politics Agency in establishing harmony in Community Organizations in Binjai City. The method used is a qualitative phenomenological approach. Meanwhile, the aim of the researcher is to explain and inform the application of the Islamic communication principles of the National and Political Unity Agency in establishing harmony with the Management of Community Organizations by applying any Islamic Communication Principles that have been used. Informants here include the Secretary to the Head of the Agency, the Head of Political Affairs, and the Secretary of Political Affairs. The results of this study indicate that the application used in the National Unity and Politics Agency is that there are six qaulan principles of Islamic communication that are applied in the National Unity and Politics Agency, namely, qaulan sadida as they apply the values ​​of truth, qaulan baligha, qaulan karima, qaulan maysura, qaulan layyina and the last one also uses qaulan ma'rufa as words or sentences that will not embarrass the communicant or himself when communicating. Keywords: Utilization of Islamic Communication Principles in Mass Organizations, Politics, and the National Unity Agency.